Effect of in concentration in the starting solution on the structural and electrical properties of ZnO films prepared by the pyrosol process at 450°C - Tokumoto, M. S. [UNESP]; Smith, A.; Santilli, Celso Valentim [UNESP]; Pulcinelli, Sandra Helena [UNESP]; Elkaim, E.; Briois, V. (Elsevier, 2000)
Undoped and indium-doped Zinc oxide (ZnO) solid films were deposited by the pyrosol process at 450°C on glass substrates from solutions where In/Zn ratio was 2, 5, and 10 at.%. Electrical measurements performed at room temperature show that the addition of indium changes the resistance of the films. The resistivities of doped films are less than non-doped ZnO films by one to two orders of magnitude depending on the dopant concentration in the solution. Preferential orientation of the films with the c-axis perpendicular to the substrate was detected by X-ray diffraction and polarized extended X-ray absorption fine structures measurements at the Zn K edge. This orientation depends on the indium concentration in the starting solution. The most textured films were obtained for solutions where In/Zn ratio was 2 and 5 at.%. When In/Zn = 10 at.%, the films had a nearly random orientation of crystallites. Evidence of the incorporation of indium in the ZnO lattice was obtained from extended X-ray absorption fine structures at the In and Zn K edges. The structural analysis of the least resistive film (Zn/In = 5 at.%) shows that In substitutes Zn in the wurtzite structure. © 2000 Elsevier Science B.V. All rights reserved.